2019
DOI: 10.3390/rs11050497
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Seasonal Effect of Building Shadows on Urban Land Surface Temperatures Based on Remote Sensing Data

Abstract: Building shadows (BSs) frequently occur in urban areas, and their area and distribution display strong seasonal variations that significantly influence the urban land surface temperature (LST). However, it remains unclear how BSs affect the LST at the city scale because it is difficult to extract the shaded area at the subpixel scale and to connect such areas with the LST at the pixel scale. In this study, we combined the sun angle, building height, building footprint and building occlusion to extract the seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 69 publications
0
25
0
2
Order By: Relevance
“…The dependence of SUHI on the urban land cover has been studied often (Weng et al, 2004;Chen et al, 2006;Yuan and Bauer, 2007;Li et al, 2016). Recently, the dependence of SUHI on the geometry of the urban built-up space has also been addressed (Yu et al, 2019). The impact of shadows determined by urban geometry has been studied by Yu et al (2019) and results showed that in Beijing the building shadow reduced by 3.16 K the temperature of the urban impervious surface in July.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of SUHI on the urban land cover has been studied often (Weng et al, 2004;Chen et al, 2006;Yuan and Bauer, 2007;Li et al, 2016). Recently, the dependence of SUHI on the geometry of the urban built-up space has also been addressed (Yu et al, 2019). The impact of shadows determined by urban geometry has been studied by Yu et al (2019) and results showed that in Beijing the building shadow reduced by 3.16 K the temperature of the urban impervious surface in July.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the dependence of SUHI on the geometry of the urban built-up space has also been addressed (Yu et al, 2019). The impact of shadows determined by urban geometry has been studied by Yu et al (2019) and results showed that in Beijing the building shadow reduced by 3.16 K the temperature of the urban impervious surface in July. More generally, the effect of urban morphology on radiometric surface temperature has been studied by Huang and Wang (2019) and the results showed that the urban geometric parameters have complex effects on the 2D and 3D pattern in urban radiometric surface temperature provided by Landsat thermal images.…”
Section: Introductionmentioning
confidence: 99%
“…In summer, building shade can cool urban temperature effectively by reducing total solar radiation in sunlight [ 38 , 39 ]. Furthermore, nearby buildings could partly be relieved from the hot sunlight owing to building shadows during the day.…”
Section: Resultsmentioning
confidence: 99%
“…Les différences constatées entre les agglomérations de Lyon et de Tokyo proviendraient des morphologies urbaines propres aux deux mégapoles. En effet, à Tokyo, la hauteur et la densité du bâti étant nettement plus élevées que sur Lyon, les bâtiments ont donc une plus grande propension à intercepter les rayons solaires et ainsi, à créer un rafraîchissement en projetant leur ombre (Zhang et al, 2017 ;Sun et al, 2019 ;Yu et al, 2019). Cela a déjà été notifié dans différentes études, surtout dans les pays du sud-est asiatique (Lin et al, 2010 ;Chan, 2012 ;Martinelli et al, 2015).…”
Section:  Les Zones D'activité Présentent Les Températures De Surfacunclassified
“…Ce phénomène n'est pas un objet d'étude récent, les premières publications remontant aux années 1990 et 2000 (Oke, 1992 ;Lam, 2000). Il est cependant toujours très difficile d'évaluer quantitativement l'impact sur le bilan énergétique à l'échelle micro-locale (Lin et al, 2017 ;Yu et al, 2019). Dans un premier temps, à Tokyo, la classe des sols nus ou sablonneux se localisent préférentiellement dans les lits majeurs des cours d'eau.…”
Section:  Les Zones D'activité Présentent Les Températures De Surfacunclassified